2012
DOI: 10.1371/journal.pone.0041404
|View full text |Cite
|
Sign up to set email alerts
|

(Pro)renin Receptor Triggers Distinct Angiotensin II-Independent Extracellular Matrix Remodeling and Deterioration of Cardiac Function

Abstract: BackgroundActivation of the renin-angiotensin-system (RAS) plays a key pathophysiological role in heart failure in patients with hypertension and myocardial infarction. However, the function of (pro)renin receptor ((P)RR) is not yet solved. We determined here the direct functional and structural effects of (P)RR in the heart.Methodology/Principal Findings(P)RR was overexpressed by using adenovirus-mediated gene delivery in normal adult rat hearts up to 2 weeks. (P)RR gene delivery into the anterior wall of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…Most importantly, our results have shown that the direct renin inhibitor aliskiren reduces the progression of VH and atherosclerosis in AngII-infused ApoE − / − mice at both sub-antihypertensive (10 mg/kg of body weight per day) and antihypertensive (50 mg/kg of body weight per day) doses. Recent work suggests that enhanced expression or activation of the PPR could have detrimental effects via AngII-independent mechanisms in both in vitro and in vivo studies [27,28]. In a relatively unique way, we focused on the efficacy of aliskiren in limiting complications of AngII infusion after the organ damage was established, rather than during this process, since this is likely to be most clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, our results have shown that the direct renin inhibitor aliskiren reduces the progression of VH and atherosclerosis in AngII-infused ApoE − / − mice at both sub-antihypertensive (10 mg/kg of body weight per day) and antihypertensive (50 mg/kg of body weight per day) doses. Recent work suggests that enhanced expression or activation of the PPR could have detrimental effects via AngII-independent mechanisms in both in vitro and in vivo studies [27,28]. In a relatively unique way, we focused on the efficacy of aliskiren in limiting complications of AngII infusion after the organ damage was established, rather than during this process, since this is likely to be most clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] On the other hand, increased PRR was observed in ischemic nephropathy, 6,7 glomerulosclerosis, 8 diabetic nephropathy, 9 diabetic retinopathy, 10 cardiac hypertrophy, 11 and heart failure. 12 In these models, the role of PRR was suggested, based on the use of a peptide that is supposed to block (pro)renin binding to PRR. But these results remain highly controversial.…”
mentioning
confidence: 99%
“…45 In contrast, overexpression of PRR in adult rat hearts via adenovirusmediated gene delivery for 2 weeks caused reduced left ventricular ejection fraction and resulted in Ang II-independent activation of cell signaling pathways. 52 Taken together, these studies suggest that either the cardiac PRR does not play a role in BP regulation or compensatory mechanisms counter any effects exerted by the increased PRR expression ( Figure 2).…”
Section: Role Of the Prr In Bp Regulationmentioning
confidence: 85%